'There Is No Alternative'? The role of depoliticisation in the emergence of populism. (August 2022) - Scott, Jake Anthony
The current literature on populism considers the causal factors surrounding the emergence of populism to be materialist and often ignores the role of elites in the precipitation of populist movements. Consequently, populism is often conceptualised as an epiphenomenon. However, it is the scope of this article that the construction of events or processes as 'beyond' public control contributes to popular resentment necessary for the emergence of populism. In comparison to this construction (encapsulated best in Margaret Thatcher's proclamation, 'there is no alternative'), democratic politics involves an appeal to the constituency most often associated with populism, 'the common people' and 'common sense'. This article, therefore, will proceed along the following lines: first, I establish the theoretical model for analysis with reference to Margaret Canovan's paper 'Trust the People!'; following this, sections ' Depoliticisation as "Pragmatic Politics"' and 'Common sense as "Redemptive Politics"' look at different permutations of the two sides of this theoretical model, respectively Depoliticisation, and an appeal to 'common sense', before turning back in the section 'Applying and illustrating the framework' to Canovan's theoretical framework to understand how the interaction between these two permutations can contribute to a populist reaction. The final section presents an illustrative example of this clash – immigration in the United Kingdom.